Colonialism in the Malay Archipelago: civilisational encounters - Bakar, Osman; Mohd Noor Merican, Ahmad Murad; Wan Mamat, Wan Ali @ Wan Yusoff (2023)
As a powerful colonial entity, the West has influenced the historical trajectory of Southeast Asia, a region often referred to as the “lands below the wind”. The arrival of Europeans transformed the region’s geopolitical, cultural, sociological, and economic features. Southeast Asia’s historical encounter with the West has thoughtfully been documented by the authors of the reviewed book. This edited volume provides a comprehensive and nuanced analysis of the encounters between Western powers and Indigenous societies. Edited and written by reputable scholars in the field of Southeast Asian history, it offers broad discussions of various historical relationships.